Retinoic Acid and Arsenic for Treating Acute Promyelocytic Leukemia - Zhou, Guang-Biao (Public Library of Science, 2005)
What were the critical steps in the development of ATRA and arsenic as treatments for APL? Researchers in Shanghai tell the story and look to the future